AUTOMATIC FISHPOND IRRIGATION DOOR CONTROL SYSTEM BASED ON ATMEGA16 MICROCONTROLLER AND SMS GATEWAY - B, Muhammad Fajar; Lestary, Fitriyanty Dwi; M. Miftach Fakhri; Muhammad Agung; Surianto, Dewi Fatmarani; Akmal Hidayat (Jurnal Teknik Informatika (Jutif), 2023)
The process of controlling irrigation doors in fishponds is still mostly done manually, this results in the performance of farmers being less effective and efficient. Current technological developments, especially in the field of IoT, can be used to design a simulation that is able to control irrigation gates automatically. Based on the results of the tests that have been carried out, it can be concluded that the ATmega16-based automatic irrigation gate simulation tool can work well according to the designed working principle. If the condition of fishpond water is less than the ideal height of the fishpond and the condition of river water is more than the height of the fishpond, the motor will move to "open" the irrigation door to fill fishpond water. If the fishpond water condition is more than the ideal height and the river water condition is less than the fishpond height, the motor will move to "open" the irrigation door to discharge fishpond water and if the river water condition is the same as the fishpond water condition, the motor will move "close” the irrigation door so that the ideal height of the fishpond can be achieved. There are certain conditions to control the door manually using the SMS Gateway. Information about the maximum or minimum fishpond water level will be displayed on the LCD to determine the maximum or minimum fishpond height using Keypad.